2011
DOI: 10.1007/s10681-010-0342-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of simple PCR-based markers linked to the Ms locus, a restorer-of-fertility gene in onion (Allium cepa L.)

Abstract: In order to implement reliable markerassisted selection systems for the restorer-of-fertility locus (Ms) in onions (Allium cepa L.), simple PCRbased codominant markers linked to the Ms locus were developed. Based on the EST probe sequences of previously reported RFLP markers, full-length genomic sequences of the gene encoding putative oligopeptide transporter (OPT) was obtained by RACE. The first intron contained two 108 and 439-bp indel polymorphisms between the two Ms allele-linked OPT alleles. A simple PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
0
23
0
3
Order By: Relevance
“…, Bang et al. ). Kim () employed these two SCAR markers and observed that marker genotyping was not clear due to the dominant nature of these two markers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, Bang et al. ). Kim () employed these two SCAR markers and observed that marker genotyping was not clear due to the dominant nature of these two markers.…”
Section: Discussionmentioning
confidence: 99%
“…We started our experiments with PCR marker OPT1 (Bang et al. ) as this marker was found to be in linkage disequilibrium in our previous studies with long‐day onion (Saini et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Bang et al. () developed PCR‐based markers from existing RFLP clones and detected one marker tightly linked to Ms , which exhibited limited linkage disequilibrium. This marker can be used to select specific alleles at Ms loci in segregating population with linkage disequilibrium, but not in diverse onion germplasm.…”
Section: Molecular Breeding In Onionmentioning
confidence: 99%